2015
DOI: 10.4172/2155-9554.1000324
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional, Clinico-Mycological Research Study of Prevalence, Aetiology, Speciation and Sensitivity of Superficial Fungal Infection in Indian Patients

Abstract: Introduction: Skin is a mechanically protective layer as well as cosmetically significant anatomical structure. The superficial cutaneous fungal infections involve its outer most covering including appendages like hair and nails. This the most common causes of skin disease in many tropical countries. Objectives: To study the prevalence, aetiology, speciation and sensitivity of superficial fungal infections. Materials and Methods: The study was conducted on 100 clinically diagnosed cases of Superficial Fungal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Dermatophytic infections are one of the most common diseases encountered by dermatologists in outpatient departments and there has been an increasing trend of dermatophytosis over the last few years in different parts of India. [12] There is a changing trend in the dermatophytic infections in that the cases are presenting as chronic, treatment unresponsive and recurrent cases. [3] This superficial fungal infection was an easily treatable condition for the practitioners previously with the commonly used antifungals.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophytic infections are one of the most common diseases encountered by dermatologists in outpatient departments and there has been an increasing trend of dermatophytosis over the last few years in different parts of India. [12] There is a changing trend in the dermatophytic infections in that the cases are presenting as chronic, treatment unresponsive and recurrent cases. [3] This superficial fungal infection was an easily treatable condition for the practitioners previously with the commonly used antifungals.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of studies done on superficial fungal infections in different cities of the country during different time frames have revealed an increasing trend of dermatophytosis. [2][3][4] India, being a tropical country, has a climate that is conducive for superficial fungal infections. The reported prevalence of dermatophytosis in India ranges from 36.6 to 78.4%.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, many studies have reported Trichophyton rubrum as the commonest isolate. [15][16][17] Another important aspect of this study was to carry out antifungal sensitivity testing of five commonly used antifungal drugs Fluconazole, Terbinafine, Itraconazole, Griseofulvin and Voriconazole. Determining the resistance pattern is especially necessary to assist clinicians in treating superficial fungal infections more effectively.…”
mentioning
confidence: 99%